Reducing barriers that prevent persons with disabilities in Uganda from accessing and utilizing WASH facilities - Bob Lubega; Job Wanakwakwa (2018)
This paper provides recommendations to address the challenges faced by persons with disabilities (PWD) in accessing and utilising water, sanitation and hygiene (WASH) facilities in Uganda. The paper has been written by the Executive Director and a colleague from the Ugandan community-based organisation Rights for Disability Development Foundation (RDDF), who are themselves PWD. It includes the status of WASH facilities in Uganda, barriers which prevent PWD accessing and utilizing suitable WASH facilities and recommendations to improve the situation. The paper is intended to inspire the diverse leaders in Uganda to upgrade WASH facilities within the country, to meet the various needs and abilities of PWD and to thereby reduce the barriers they face.